2015
DOI: 10.1016/j.chemosphere.2014.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Energy-based modelling to assess effects of chemicals on Caenorhabditis elegans: A case study on uranium

Abstract: International audienceThe ubiquitous free-living nematode Caenorhabditis elegans is a powerful animal model for measuring the evolutionary effects of pollutants which is increasingly used in (eco)toxicological studies. Indeed, toxicity tests with this nematode can provide in a few days data on the whole life cycle. These data can be analysed with mathematical tools such as toxicokinetic-toxicodynamic modelling approaches. In this study, we assessed how a chronic exposure to a radioactive heavy metal (uranium) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 42 publications
0
29
0
Order By: Relevance
“…Growing faster and becoming larger may allow individuals to detoxify their bodies, prevent internalization of the pollutant and reduce internal pollutant concentrations (Guedes et al., 2006; Sibly & Calow, 1989). For example, uranium severely affects the intestinal epithelium in the earthworm, Eisenia fetida (Giovanetti et al., 2010) and seems to decrease energy assimilation in C. elegans (Goussen et al., 2015). The presence of uranium in the environment increases the expression of metallothionein‐1 (mtl‐1), which interferes with U accumulation in cells, probably by sequestering and removing uranium from the cells (Jiang et al., 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Growing faster and becoming larger may allow individuals to detoxify their bodies, prevent internalization of the pollutant and reduce internal pollutant concentrations (Guedes et al., 2006; Sibly & Calow, 1989). For example, uranium severely affects the intestinal epithelium in the earthworm, Eisenia fetida (Giovanetti et al., 2010) and seems to decrease energy assimilation in C. elegans (Goussen et al., 2015). The presence of uranium in the environment increases the expression of metallothionein‐1 (mtl‐1), which interferes with U accumulation in cells, probably by sequestering and removing uranium from the cells (Jiang et al., 2009).…”
Section: Discussionmentioning
confidence: 99%
“…It accumulates in the cells and affects the intestinal epithelium (Giovanetti, Fesenko, Cozzella, Asencio, & Sansone, 2010), thus reducing energy and nutrient assimilation. In C. elegans , uranium is assumed to decrease the assimilation of energy from food (Goussen et al., 2015). Salt concentration has recently increased in several ecosystems with important sources of salt originating from winter road maintenance, wastewater and intensive irrigation (e.g., Dugan et al., 2017; Müller & Gächter, 2012; Rengasamy, 2006; Verwey & Vermeulen, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The three others have indirect effects on the reproduction in conjunction with effects on growth (assimilation, maintenance, and growth models). Our previous study demonstrated that the mode of action of the uranium on C. elegans is likely to be a decrease of energy assimilation from food 36 …”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…37,75 However, it has been found that some of these physiological parameters do not have significant influence on sublethal endpoints, such as growth and reproduction, in worms. 75 It has been suggested that variations in any TBTK data set could be associated with biological variation, experimental, and analytical errors. 76 To determine biomass of small organisms more rigorously, a previous study proposed a method by using tissue-element contents as a proxy for biomass determination.…”
Section: Limitations and Implicationsmentioning
confidence: 99%
“…81 It was found that uranium affected assimilation of energy from food and disrupted growth and reproduction in C. elegans based on the DEBtox model. 75 Taken together, although there are plausible uncertainties in the experiments and the modeling, our toxicity bioassays and the TBTK/TD modeling in worms could be extensively applied in environmental and health-risk analysis. By adopting exposure-and field-based information of Fe 0 NPs, the concentration-response relationships constructed in worms will make substantial progress in a quantitative risk assessment.…”
Section: Limitations and Implicationsmentioning
confidence: 99%